Practice of wound closure techniques among emergency physicians and surgeons in Makkah City Hospitals in Saudi Arabia - Jeehad Felemban; Kenan A Binyaseen; Waleed S Almalki; Fahad S Altowairqi; Amer O Sakhakhini; Ziyad I Alharbi (SAGE Publishing, 2021)
Background: Wound suturing is a procedure performed by medical and surgical specialists. While there are many different suturing techniques and materials used to treat patients, the choice of which to employ depends on different variables that affect the outcome of the procedure. Design and Methods: This is a cross-sectional study conducted to provide descriptive data regarding the practice of wound closure techniques, and to develop an awareness of scar formation factors. A total of 172 general surgery (GS) surgeons and emergency (EM) physicians in Makkah city hospitals in Saudi Arabia participated in the study. Results: More than 50% of the practitioners favored the simple interrupted technique for the treatment of all types of studied wounds. The other most common techniques among participants were the subcuticular and vertical mattress methods, respectively, while the use of a stapler was limited to certain wound types. Regarding suturing material, polyglycolic acid was the most frequent material used by 50.1% of participants, whereas only 22% of the participants selected nylon material for wound suturing. However, this study showed a good level of awareness among participants, with significant p-values (p<0.05) of strongly agree and agree regarding the essential factors affecting wound healing and scar formation. Conclusions: The result provides insight into the most common suture techniques and materials used in wound closure. There are wide variations in selecting these techniques and materials among the participants. Also, we found that there is good awareness among participants about factors that lead to scar formation.